Expression of National Mentality through Somatic Units in Uzbek and English Proverbs (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Proverbs, often considered a mirror of a nation's cultural identity, encapsulate the values, beliefs, and worldview of its people. Somatic (body-related) expressions in proverbs are particularly insightful in revealing how bodily metaphors shape national mentalities. This paper explores the role of somatic units in Uzbek and English proverbs, comparing how body-related metaphors reflect cultural and social norms in both languages. The study examines how these expressions contribute to the understanding of mentality, focusing on similarities and differences in how bodily imagery is used to convey meaning, wisdom, and social expectations in both linguistic traditions. Furthermore, the paper discusses the cultural characteristics embedded in somatic proverbs and how they inform the larger concept of national mentality.